2006
DOI: 10.1177/0363546506288728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Apparent and Absolute Supraspinatus Strength in Patients with Shoulder Injury Using the Scapular Retraction Test

Abstract: The clinical examination that addresses scapular posture and includes scapular retraction will allow more accurate determination of absolute supraspinatus muscle strength and allow efficacious rehabilitation protocols to address the source of the demonstrated weakness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
125
2
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 212 publications
(138 citation statements)
references
References 20 publications
(24 reference statements)
4
125
2
7
Order By: Relevance
“…Kibler et al 21 have reported on the effect of a similar repositioning maneuver, the Scapula Retraction Test, using what is described as a "proprioceptive reminder" via minimal forearm pressure on the scapula during the same isometric resisted elevation task used in this study. They reported a 24% mean increase in strength between the empty can in the natural posture and repositioned test in symptomatic subjects, with all 20 symptomatic subjects demonstrating strength gains with repositioning.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Kibler et al 21 have reported on the effect of a similar repositioning maneuver, the Scapula Retraction Test, using what is described as a "proprioceptive reminder" via minimal forearm pressure on the scapula during the same isometric resisted elevation task used in this study. They reported a 24% mean increase in strength between the empty can in the natural posture and repositioned test in symptomatic subjects, with all 20 symptomatic subjects demonstrating strength gains with repositioning.…”
Section: Discussionmentioning
confidence: 87%
“…First, our subjects with impingement represented a subclinical, college-age population, some of whom were asymptomatic except with provocation testing, while others had only mild symptoms. The subjects in the Kibler et al 21 study were older with a wide age range (mean  SD, 43  16 years) and had diagnoses of labral injury, glenohumeral instability, or impingement with medical imaging (MRI) evidence of pathology, and were described as having decreased supraspinatus strength and scapular dyskinesis on clinical exam. Of the 142 subjects in our study, less than one third demonstrated scapular dyskinesis, as determined by a visual classification system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations